Adding self-explanation when learning goal free problems could be beneficial - Sendy Hidayah; Endah Retnowati; Ng Khar Thoe (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2025)
Goal free problem is a strategy to present a geometrical problem by removing the final goal in order to direct students not to use a means ends analysis. The purpose of this research was to examine whether adding self-explanation instruction could improve its effectiveness with regard to students' problem-solving abilities and cognitive load. Using Geometry (the relationship among angles) as part of the national curriculum, a quasi-experimental research was employed. The post-test only group experimental design, comparing studying with self-explanation and without self-explanation, involved sixty four seven-graders from four parallel authentic classrooms in a junior high school in Central Java, Indonesia while the previous math test score was used as covariate. The covariate did not have ssignificant linierity meaning that both experimental groups were randomly assigned and had indifferent level of prior knowledge before the experiment was executed. The overall evidence indicated that with or without self-explanation, both groups of students who were given goal free problems did not have significant difference in terms of problem-solving abilities. However, there was a significant difference on level of cognitive load. Learning goal free problems with self-explanation could be more effective because this strategy causes a lower cognitive load than those without self-explanation. This study suggests that the instruction of self-explanation might lower extraneous cognitive load and improve learning.